Ukraine : Financial System Stability Assessment, including Reports on the Observance of Standards and Codes on the following topics; Monetary and Financial Policy Transparency, Banking Supervision, and Payment Systems. (IMF Staff Country Reports; Country Report ;, 2003)
This Financial System Stability Assessment paper for Ukraine reviews financial sector issues and highlights macroeconomic developments, vulnerabilities, and soundness of the financial system. It discusses creditors' rights, insolvency, and corporate governance, and Anti-Money Laundering and Combating of Financing Terrorism. It provides information on the observance of international standards and codes, and the compliance with the Basel Core Principle for Effective Banking. It also reviews Ukraine's observance of good transparency practices in monetary and financial policies, including payments system oversight, banking supervision, and deposit insurance supervision.